The association of hyponatremia with morbidity and mortality: A retrospective study on older hospitalized adults / Tan In Jiann - Tan, In Jiann (2018)
Hyponatremia is one of the most common electrolyte disorders to affect the older persons and is associated with impaired quality of life and survival. With the acceleration of population ageing especially in developing nations, hyponatremia would likely post a greater strain on the running of coasts of the healthcare system. The aim of this study was to investigate hyponatremia associated clinical characteristics of hospitalized geriatric patients and association with morbidity and mortality.